Analisis Pengaruh Keragaman Menu, Daya Tarik Promosi, Dan Lokasi Terhadap Minat Beli Konsumen Pada Pizza Hut Cabang Bintaro Plaza Tangerang Selatan - Albiansyah, Albiansyah; Handayani, Ragil Oktavia (Sekolah Tinggi Ilmu Ekonomi Bhakti Pembangunan, 2024)
This research aims to determine the influence of the variables Menu Diversity, Promotional Attractiveness, and Location on Consumer Purchase Interest at Pizza Hut Bintaro Branch, South Tangerang. Research data sources are data sources needed to conduct research. These data sources can be obtained either directly, called primary data or indirectly or called secondary data related to the research object. Meanwhile, the types of data used in this research are primary data and secondary data. The population in this study were visitors who ordered at the Pizza Hut Bintaro branch, South Tangerang. This research uses an accidental sampling technique which aims to obtain samples by chance to be more efficient in sample collection, to take the number of samples using the saturated sample method. The analytical method used in this research is multiple linear regression which is used to test the influence of Menu Diversity, Promotional Attractiveness, and Location which are independent variables on Consumer Buying Interest which is the dependent variable. Data processing in this research used the Statistical Program for Social Science (SPSS) version 25.0 for Windows. From the results of the t test analysis with a significance level of 5%, it shows that the variables Menu Diversity, Promotional Attractiveness and Location have a partial positive and significant effect on Consumer Purchase Interest. The results of the F test analysis of the variables Menu Diversity, Promotional Attractiveness, and Location have a positive and significant effect on Consumer Purchase Interest simultaneously. The predictive ability of the three independent variables (Menu Diversity, Promotional Attractiveness, and Location) on the dependent variable (Consumer Purchase Interest) in this research is 66.5% while the remaining 33.5% is explained by other variables outside the research model.